WNT16 is robustly increased by oncostatin m in mouse calvarial osteoblasts and acts as a negative feedback regulator of osteoclast formation induced by oncostatin M - Henning, Petra; Movérare-Skrtic, Sofia; Westerlund, Anna; de Souza, Pedro Paulo Chaves [UNESP]; Floriano-Marcelino, Thais [UNESP]; Nilsson, Karin H.; El Shahawy, Maha; Ohlsson, Claes; Lerner, Ulf H. (My University, 2021)
Background: Bone loss is often observed adjacent to inflammatory processes. The WNT signaling pathways have been implicated as novel regulators of both immune responses and bone metabolism. WNT16 is important for cortical bone mass by inhibiting osteoclast differentiation, and we have here investigated the regulation of WNT16 by several members of the pro-inflammatory gp130 cytokine family. Methods: The expression and regulation of Wnt16 in primary murine cells were studied by qPCR, scRNAseq and in situ hybridization. Signaling pathways were studied by siRNA silencing. The importance of oncostatin M (OSM)-induced WNT16 expression for osteo-clastogenesis was studied in cells from Wnt16-deficient and wild-type mice. Results: We found that IL-6/sIL-6R and OSM induce the expression of Wnt16 in primary mouse calvarial osteoblasts, with OSM being the most robust stimulator. The induction of Wnt16 by OSM was dependent on gp130 and OSM receptor (OSMR), and downstream signaling by the SHC1/STAT3 pathway, but independent of ERK. Stimulation of the calvarial cells with OSM resulted in enhanced numbers of mature, oversized osteoclasts when cells were isolated from Wnt16 deficient mice compared to cells from wild-type mice. OSM did not affect Wnt16 mRNA expression in bone marrow cell cultures, explained by the finding that Wnt16 and Osmr are expressed in distinctly different cells in bone marrow, nor was osteoclast differentiation different in OSM-stimulated bone marrow cell cultures isolated from Wnt16−/- or wild-type mice. Furthermore, we found that Wnt16 expression is substan-tially lower in cells from bone marrow compared to calvarial osteoblasts. Conclusion: These findings demonstrate that OSM is a robust stimulator of Wnt16 mRNA in calvarial osteoblasts and that WNT16 acts as a negative feedback regulator of OSM-induced osteoclast formation in the calvarial bone cells, but not in the bone marrow.
Keywords: Oncostatin M; Osteoblast; Osteoclast; WNT16